2015
DOI: 10.1136/bjsports-2015-094953
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral health including active caries in 187 UK professional male football players: clinical dental examination performed by dentists

Abstract: This is the first large, representative sample study in professional football. Oral health of professional footballers is poor, and this impacts on well-being and performance. Successful strategies to promote oral health within professional football are urgently needed, and research should investigate models based on best evidence for behaviour change and implementation science. Furthermore, this study provides strong evidence to support oral health screening within professional football.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
2
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 21 publications
4
60
2
9
Order By: Relevance
“…Nine different athlete-reported outcome measures were used in ten observational (epidemiological or surveillance) studies [26, 27, 29, 30, 33, 35, 39, 40, 42, 46]. However, most were designed for use in individual studies without reference to evidence of validity.…”
Section: Resultsmentioning
confidence: 99%
“…Nine different athlete-reported outcome measures were used in ten observational (epidemiological or surveillance) studies [26, 27, 29, 30, 33, 35, 39, 40, 42, 46]. However, most were designed for use in individual studies without reference to evidence of validity.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that participants with excessive TV viewing showed a higher prevalence of dental caries among schoolchildren in China (Zeng et al 2014). Given that dental caries are adversely associated with the frequency of toothbrushing (Murtomaa 1979;Macgregor et al 1996;Eisalhy et al 2015;Needleman et al 2016), excessive TV viewing could also be associated with a lower brushing frequency. However, our results showed an adverse impact of game-playing, but not TV viewing on toothbrushing frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is one of the most important concerns among athletes due to a high prevalence of dental trauma and diseases, such as dental caries, erosion, and periodontal disease (Ashley et al 2015;Inouye and McGrew 2015;Needleman et al 2016). Although oral conditions have direct impacts on sports performance (Ashley et al 2015), athletes tend to receive examinations/treatments only when needed, and do not attend regular check-ups due to low oral health literacy (Hanke-Herrero et al 2013;McGovern et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have shown that elite human athletes report dental disease has a negative impact on their performance (Needleman et al 2013(Needleman et al , 2016. Therefore, we propose that malocclusion might also impact the performance of sport horses.…”
Section: Introductionmentioning
confidence: 87%